1996
DOI: 10.1182/blood.v88.1.146.bloodjournal881146
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil rolling, arrest, and transmigration across activated, surface-adherent platelets via sequential action of P-selectin and the beta 2-integrin CD11b/CD18

Abstract: Platelets bound to thrombogenic surfaces have been shown to support activation-dependent firm adhesion of neutrophils in flow following selectin-mediated tethering and rolling. The specific receptor(s) responsible for mediating adhesion-strengthening interactions between neutrophils and platelets has not previously been identified. Furthermore, the ability of adherent platelets to support the migration of bound neutrophils has not been tested. We studied neutrophil interactions with activated, surface-adherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
154
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(159 citation statements)
references
References 0 publications
1
154
0
4
Order By: Relevance
“…The previous literature is complex and partly contradictory with respect to the role of individual β 2 ‐integrins in leukocyte adhesion, and the importance of LFA‐1 and Mac‐1 appears to vary depending on the type of inflammatory stimulus and experimental model ( Argenbright et al , 1991 ; Issekutz & Issekutz, 1992; Tanaka et al , 1993 ; Rutter et al , 1994 ; Diacovo et al , 1996 ; Kunkel et al , 1996 ; Schmits et al , 1996 ; Lu et al , 1997 ; Ding et al , 1999 ; Thorlacius et al , 2000 ; Dunne et al , 2002 ; Riaz et al , 2002 ). These discrepancies cannot be resolved at present, but may be related to the use of different Ab preparations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous literature is complex and partly contradictory with respect to the role of individual β 2 ‐integrins in leukocyte adhesion, and the importance of LFA‐1 and Mac‐1 appears to vary depending on the type of inflammatory stimulus and experimental model ( Argenbright et al , 1991 ; Issekutz & Issekutz, 1992; Tanaka et al , 1993 ; Rutter et al , 1994 ; Diacovo et al , 1996 ; Kunkel et al , 1996 ; Schmits et al , 1996 ; Lu et al , 1997 ; Ding et al , 1999 ; Thorlacius et al , 2000 ; Dunne et al , 2002 ; Riaz et al , 2002 ). These discrepancies cannot be resolved at present, but may be related to the use of different Ab preparations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Based on experiments using antibody (AB) treatment, it has been reported that both LFA‐1 (CD11a/CD18) and Mac‐1 (CD11b/CD18) can mediate chemoattractant‐induced leukocyte adhesion. However, the relative importance appears to be both stimulus‐ and organ‐dependent ( Argenbright et al , 1991 ; Morisaki et al , 1991 ; Issekutz & Issekutz, 1992; Tanaka et al , 1993 ; Rutter et al , 1994 ; Diacovo et al , 1996 ; Schmits et al , 1996 ; Lu et al , 1997 ; Ding et al , 1999 ; Thorlacius et al , 2000 ; Dunne et al , 2002 ). Moreover, the current complex and controversial data regarding the role of individual β 2 ‐integrins in leukocyte–endothelial cell interactions might be attributed to the use of individual monoclonal antibodies recognizing different epitopes, as well as to the use of either complete antibodies or Fab fragments.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that Îł ‐aminobutyric‐WVDW, a P‐selectin antagonist ( Appeldoorn et al ., 2003 ), inhibited PLA indicating that this receptor plays a critical role in PAR agonist‐stimulated PLA. Although selectins mediate initial margination and rolling, activated β 2 ‐integrins are necessary for stable adhesion and spreading of leukocytes on the immobilized platelets ( Diacovo et al ., 1996 ; Kuijper et al ., 1996 ; 1998 ; Weber & Springer, 1997 ; Gahmberg et al ., 1998 ; Simon et al ., 2000 ; Santoso et al ., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leucocyte recruitment through tethering, rolling, firm adhesion and transmigration on endothelium is a well recognized event in inflammation21. This may also occur on a layer of adherent, activated platelets covering either exposed subendothelial connective tissue or activated endothelium4, 10, 22. Platelet interactions via receptors and soluble factors lead to recruitment of leucocytes into areas of vascular injury and mutual activation.…”
Section: Platelets and Inflammationmentioning
confidence: 99%